Effectiveness of 7-day triple therapy with half-dose clarithromycin for the eradication of Helicobacter pylori without the A2143G and A2142G point mutations of the 23S rRNA gene in a high clarithromycin resistance area - Cho, Seong Hyun; Park, Moon Sik; Park, Seon-Young; Kim, Dong Hyun; You, Hye-Su; Kim, Hyun-Soo (Frontiers in Medicine, 2023)
Background: Tailored therapy based on dual priming oligonucleotide-based polymerase chain reaction (DPO-PCR) has been widely used for patients with Helicobacter pylori (H. pylori) infection in South Korea. Herein we evaluated the treatment outcomes of clarithromycin-based triple therapy (TT) in patients with H. pylori without a point mutation by DPO-PCR in real clinical practice. Methods: We enrolled 460 patients without 23S rRNA point mutation who had taken TT and undergone the urease breath test to evaluate eradication. Eradication rates according to the treatment duration and dose of clarithromycin were analyzed. Results: Among 460 patients (164 women, mean age 63.1 ± 10.3 years.), 250 and 216 had taken TT with full-dose clarithromycin (TT-full CLA) and TT with half-dose clarithromycin (TT-half CLA), respectively. The over eradication rates were 88.0% (220/250) in patients with TT-full CLA and 85.2% (179/210) in patients with TT-half CLA. In 250 patients with TT-full CLA, the eradication rates were 86.8% (33/38) in patients with 7-day TT-full CLA and 88.2% (187/212) in patients with 10-day or 14d TT-full CLA (P = 0.788). In 210 patients with TT-half CLA, the eradication rates were 84.2% (139/165) in those with a 7-day TT-half CLA and 88.9% (40/45) in those with a 10 or 14-day TT-half CLA (P = 0.436). Conclusion: For patients with H. pylori infection without a 23S rRNA point mutation, treatment extension above 7-day TT with full CLA did not improve the eradication rates. Future studies on the treatment outcomes of TT-half CLA considering effectiveness and compliance are warranted.